Multicentre study of the impact of factors that may affect long-term survival following pancreaticoduodenectomy for distal cholangiocarcinoma. Issue 5 (May 2018) - Courtin-Tanguy, Laëtitia; Turrini, Olivier; Bergeat, Damien; Truant, Stéphanie; Darnis, Benjamin; Delpero, Jean R.; Mabrut, Jean Y.; Regenet, Nicolas; Sulpice, Laurent
Abstract: Background: Although the peri-operative mortality following pancreaticoduodenectomy (PD) for distal cholangiocarcinoma (DCC) has decreased, the post-operative morbidity remains high. The aim of this study was to evaluate the impact of factors that may affect the long term survival for patients with DCC following PD. Methods: All patients who underwent PD for DCC between January 2000 and December 2015 in 5 tertiary referral centers underwent retrospective medical record review. Factors likely to influence overall (OS) and disease-free (DFS) survivals were assessed by univariate and multivariate analysis. Results: A total of 201 on 217 patients who underwent PD for DCC were included for further analysis. The median OS was 39 months, with actuarial survival rates at 1, 3, and 5 years of 85%, 53% and 39%. Recurrence occurred in 123 (61%) patients. The median DFS was 16 months, with actuarial survival rates at 1, 3 and 5 years of 60%, 37% and 28%. Following multivariate analysis, peri-operative blood transfusions (PBT) were associated to worse OS (HR = 2.25 [1.31–3.85], P  = 0.003) and DFS (HR = 2.08 [1.24–3.5], P  = 0.005). Conclusion: This study confirms the negative impact of PBT on the oncologic result following PD for DCC.